2017
DOI: 10.5487/tr.2017.33.4.265
|View full text |Cite
|
Sign up to set email alerts
|

Error-Prone and Error-Free Translesion DNA Synthesis over Site-Specifically Created DNA Adducts of Aryl Hydrocarbons (3-Nitrobenzanthrone and 4-Aminobiphenyl)

Abstract: Aryl hydrocarbons such as 3-nitrobenzanthrone (NBA), 4-aminobiphenyl (ABP), acetylaminofluorene (AAF), benzo(a)pyrene (BaP), and 1-nitropyrene (NP) form bulky DNA adducts when absorbed by mammalian cells. These chemicals are metabolically activated to reactive forms in mammalian cells and preferentially get attached covalently to the N2 or C8 positions of guanine or the N6 position of adenine. The proportion of N2 and C8 guanine adducts in DNA differs among chemicals. Although these adducts block DNA replicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Pol κ is inhibited by the major groove adducts BPDE- N 6 -dA [14], N 6 -furfuryl-dA [48], and bulky O 6 -alkyl-dG modifications [49,50]. Pol κ can replicate DNA templates containing various bulky and non-bulky lesions, such as BPDE- N 2 -dG [10,14,16,17,51,52,53,54,55], N 2 -(1-carboxyethyl)-dG [56,57], 8-oxo-dG [17], N 2 -alkyl-dG [10,58], O 2 - and some O 4 -alkyl-dT adducts [59,60,61,62], thymine glycol [45], DNA-peptide crosslinks, and intrastrand adducts and interstrand crosslinks (ICL) formed between purine bases and cisplatin [6,10,17,63,64,65,66,67,68,69,70].…”
Section: Fidelity and Selectivitymentioning
confidence: 99%
“…Pol κ is inhibited by the major groove adducts BPDE- N 6 -dA [14], N 6 -furfuryl-dA [48], and bulky O 6 -alkyl-dG modifications [49,50]. Pol κ can replicate DNA templates containing various bulky and non-bulky lesions, such as BPDE- N 2 -dG [10,14,16,17,51,52,53,54,55], N 2 -(1-carboxyethyl)-dG [56,57], 8-oxo-dG [17], N 2 -alkyl-dG [10,58], O 2 - and some O 4 -alkyl-dT adducts [59,60,61,62], thymine glycol [45], DNA-peptide crosslinks, and intrastrand adducts and interstrand crosslinks (ICL) formed between purine bases and cisplatin [6,10,17,63,64,65,66,67,68,69,70].…”
Section: Fidelity and Selectivitymentioning
confidence: 99%
“…The recruitment of these polymerases, which leave distinct mutation patterns are dependent on the nature of the blocking lesion. Depending on the blocking lesions, translesion synthesis (TLS) performed by Pol η, κ, ι, and ζ and Rev1 may be error-free or error-prone [43]. For abasic sites formed from depurination, TLS yields deletions and A misincorporation opposite the non-cognate lesion [44].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that compared with other cancers, the ABP-induced mutations are more evenly distributed along the p53 gene and the mutation hotspots occur through the genome with the major mutation being G to T transversion [21,22]. TLS over dG-C8-ABP in two different sequences (CCG*GAGGC and CCGGAG*GCC, G* = dG-C8-ABP), which represent codon 248 and 249 sequences of the human p53 tumor suppressor gene, respectively, has confirmed that codon 248 is a hot spot for adduct formation and G to T mutation.…”
Section: Discussionmentioning
confidence: 99%
“…The major induced mutation is a G to T transversion mutation. Translesion synthesis (TLS) over dG-C8-ABP in two different sequences (CCG*GAGGC and CCGGAG*GCC, G* = dG-C8-ABP), which represent the codon 248 and 249 sequences of the human p53 tumor suppressor gene, respectively, has confirmed that codon 248 is both a hot spot of ABP adduct formation and G to T mutation [22]. These results suggest that the efficiency of TLS over dG-C8-ABP is influenced by the surrounding DNA sequences.…”
Section: Introductionmentioning
confidence: 99%